Polydatin enhances oxaliplatin-induced cell death by activating NOX5-ROS-mediated DNA damage and ER stress in colon cancer cells - Qi Zhao; Qi Zhao; Qi Zhao; Yan Zhang; Yan Zhang; Jieyu Liu; Peipei Chen; Annabeth Onga; Namki Cho; Ri Cui; Chenguo Zheng (Frontiers in Pharmacology)
BackgroundPolydatin (3,4′,5-trihydroxy-3-β-d-glucopyranoside, PD) is known for its antioxidant and anti-inflammatory properties. Oxaliplatin (OXA)-based chemotherapy is the first-line treatment for metastatic and recurrent colorectal cancer (CRC). However, the lack of selectivity for normal cells often results in side effects. Consequently, the search for anti-cancer components with high efficacy and low cytotoxicity has become a significant focus in recent years.MethodsThe anti-tumor effects of PD, OXA or their combination were assessed by cell viability, colony formation, and wound-healing assays. Reactive oxygen species (ROS) generation was measured by flow cytometry and DNA damage was assessed by immunofluorescence assay. The relative gene and protein expressions were analyzed by quantitative real time-PCR (qRT-PCR) and Western blot assays. Molecular docking analysis predicted the interaction between PD and potential targets.ResultsWe found that PD exerted anti-CRC activity by promoting Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidase 5 (NOX5)-mediated ROS production, activating the endoplasmic reticulum (ER) stress, and inducing DNA damage. Knocking down NOX5 attenuated the inhibition of proliferation and colony forming ability induced by PD in colon cancer cells and reversed the expression of C/EBP-homologous protein (CHOP) and activating transcription factor 4 (ATF4) proteins. In addition, combination of PD and OXA synergistically exerted anti-CRC activities by promoting DNA damage and activating ER stress signaling pathway.ConclusionThe combination of PD and OXA could be an effective treatment strategy for certain patients with CRC.